Enhancing Service Quality and Student Loyalty in Higher Education Using Blockchain Technology - Ayun Maduwinarti; I.G.N. Andhika Mahendra; Dwi Cahyono; Cristino Gusmao; Chua Toh Hua (IAIC Bangun Bangsa, 2025)
In the increasingly digital era demanding transparency, blockchain emerges as a technology with significant potential to support higher education services. This system offers security, efficiency, and decentralization in managing academic data and certifications. This study aims to examine the role of blockchain in improving service quality and student loyalty. Data were collected through interviews and FGDs with participants from students, faculty, and administrative staff relevant to the technology's implementation in their institutions. The findings show positive acceptance of blockchain, especially in terms of transparency and service speed. Participants also suggested digital incentives through a token system as a way to encourage active student engagement. However, challenges such as infrastructure, technological literacy, and regulations remain major obstacles. These results reinforce that blockchain can improve service quality and create loyalty based on a fair and measurable system.